2014
DOI: 10.1186/s40555-014-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in body size and age structure of the Sauter’s frog Rana sauteri in Taiwan

Abstract: Background: The tendency for organisms to be larger in cooler climates, the so-called Bergmann's rule, has been widely observed in endotherms, but it is debatable in ectothermic anurans. Altitudinal variations in body size, age, and growth rate of the Sauter's frog Rana sauteri were investigated with skeletochronology at six sites along the altitudinal gradients from 330 to 2,320 m in subtropical Taiwan. The aims of this study were to determine whether these life history traits vary with altitude and differ be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
3
13
1
1
Order By: Relevance
“…However, no significant difference in the SVL of mature frogs was detected in the two populations. Previous studies suggested that differences in body size and age structure between populations often occur due to differences in altitude or latitude (e.g., Sagor et al, 1998;Hsu et al, 2014). For example, age at sexual maturity, longevity, and body size tend to be greater at higher altitudes compared to lower altitudes in many amphibians (Morrison and Hero, 2003).…”
Section: Comparison Between the Two Populationsmentioning
confidence: 99%
“…However, no significant difference in the SVL of mature frogs was detected in the two populations. Previous studies suggested that differences in body size and age structure between populations often occur due to differences in altitude or latitude (e.g., Sagor et al, 1998;Hsu et al, 2014). For example, age at sexual maturity, longevity, and body size tend to be greater at higher altitudes compared to lower altitudes in many amphibians (Morrison and Hero, 2003).…”
Section: Comparison Between the Two Populationsmentioning
confidence: 99%
“…Some of them have been mentioned and include the age at maturity, longevity, clutch size, egg size, larval period, food availability, substrate, etc. (Morrison & Hero 2003;Sinsch et al 2010;Oromi et al 2012;Hsu et al 2014;Davenport & Hossack 2016).…”
Section: Body Size Variationmentioning
confidence: 99%
“…On the other hand, several authors have demonstrated a geographic trend in body size and SSD within species, some with some environmental variables as explaining factors, other with no relationship (Nevo 1973;Sch€ auble 2004;Laugen et al 2005;Cvetkovic et al 2008;Yu et al 2010;Oromi et al 2012;Hsu et al 2014;Feng et al 2015;Valenzuela-S anchez et al 2015;Davenport & Hossack 2016;Gouveia & Correia 2016). Also, differences in age at maturity, longevity, growth rates, or substrate could also account for population divergence (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De acuerdo con la hipótesis de la selección sexual, el dimorfismo surge de la competencia por la pareja y se atribuye a la diferencia sexual en los roles reproductivos (Seglie et al, 2010). Para los anuros, la direccion del SSD hacia uno u otro sexo ha sido ampliamente discutida y relacionada con tres procesos de selección: selección sexual tanto a traves de competencia intrasexual macho-macho como eleccion intersexual de la hembra (Darwin, 1874;Woolbright, 1983;Andersson, 1994); selección natural cuando los sexos utilizan recursos o respoden a condiciones ambientales de manera diferencial o las poblaciones experimentan diferentes ambientes (hipotesis de plasticidad diferencial; Katsikaros y Shine, 1997;Angilletta y Dunham, 2003;Hsu et al, 2014;Laiolo et al, 2013;Zhang y Lu, 2013); y, por ultimo, selección de fertilidad, siendo que un tamaño corporal grande en las hembras confiere una ventaja reproductiva debido a la relacion positiva entre volumen de la puesta, tamaño del huevo, y tamaño corporal (Crump, 1974;Han y Fu, 2013;Liao et al, 2015). Esto último se produce debido a que las hembras asignan la mayor parte de su esfuerzo reproductivo a producir gametos, relativamente grandes y en menor cantidad y, como consecuencia, el tamaño de la misma tiene un efecto positivo y constante sobre su potencial esfuerzo reproductivo.…”
Section: Dimorfismo Sexual En El Tamaño Corporal (Ssd)unclassified